Two new species of the armored catfish genus Panaqolus (Siluriformes, Loricariidae) from the Ecuadorian Amazon - Provenzano-Rizzi, Francisco; Barriga-Salazar, Ramiro; Stewart, Donald J. (Zootaxa, 2024)
Currently four described species of genus Panaqolus have been reported from the Amazon River basin in Ecuador: P. albomaculatus (Kanazawa 1958), P. dentex (Günther 1868), P. gnomus (Schaefer & Stewart 1993) and P. nocturnus (Schaefer & Stewart 1993). Revision of specimens deposited at the fish collection of Museo de la Escuela Politécnica Nacional (MEPN), Quito, indicated the presence of two additional species, both new to science: P. orcesi n. sp. and P. pantostiktos n. sp. The new species are similar to each other, and to P. albomaculatus and P. nix Cramer & Rapp Py-Daniel 2015 in having the head, body, and fins covered with light dots. Diagnostic characters comprise differences in color pattern, including size and density of light dots on head, body, and fins; as well as various morphometric characters. Apparently, both new species reach larger sizes than previously described species of Panaqolus. The two new species can be included in the subgenus Panafilus (Lujan et al. 2017); they come from the Tigre and Napo River basins, two isolated tributaries in the western Amazon.